Prophetic And Moral Values In The Folk Tale Of Dodeng Lebonna - Kristiani Tandi Rani; Siti Nurbaya; Suroso (Cita konsultindo, 2025)
This study explores the prophetic aspects and moral values in the folklore Dodeng Lebonna using Creswell's phenomenological method. This folklore is part of the oral tradition of the Tana Toraja community, rich in life values relevant to the socio-cultural context. The aim of this study is to understand the experiences and meanings perceived by individuals regarding the element of sacrifice in the story, conveyed through symbolism, narrative structure, and language choices. Through a phenomenological approach, this research delves into deep perceptions and interpretations of moral values such as honesty, sincerity, and social responsibility, embodied in the dialogues and actions of the main characters. The findings reveal that Dodeng Lebonna reflects sacrifice as a manifestation of prophetic and moral values. This study highlights the crucial role of folklore as a medium for moral education across generations amidst the tide of modern cultural changes.